The Influence of Data-Based HR Management on the Quality of Employment Decisions with the Mediation of Employee Data Literacy - Suwandi, Suwandi (Universitas Syiah Kuala, 2025)
The development of information technology has driven a paradigm shift in human resource management (HRM), from a conventional approach to data-based management. This study aims to analyze the effect of data-based HRM on the quality of employment decisions with employee data literacy mediation. Using a quantitative approach and Structural Equation Modeling (SEM) analysis techniques, data were collected through a survey of six HR practitioners from three companies (PT. X, Y, and Z) that have implemented data-based HR. The results of the analysis indicate that the use of data in recruitment, workforce planning, and performance management has a positive impact on improving the quality of decisions, especially in terms of recruitment accuracy, employee retention, and performance improvement. The findings also reveal that employee data literacy significantly mediates the relationship between data-based HRM and the quality of employment decisions. Dimensions of data literacy such as data interpretation and use are proven to support evidence-based decision making. This study strengthens the relevance of the Resource-Based View and Human Capital Theory theories, and shows the importance of organizational investment in data technology and employee literacy development. The practical implications of these findings emphasize the need for a comprehensive data literacy improvement strategy across all levels of the organization.